Does fiscal austerity affect public opinion? - Anna Kalbhenn; Livio Stracca (European Central Bank (ECB), 2015)
In this paper we explore the impact of fiscal austerity on three different dimensions of public opinion (overall life satisfaction and confidence, attitude towards national authorities, and European institutions). Based on a panel of 26 EU countries, we find that, overall, fiscal consolidation episodes tend to have little and inconsistent impact on our measures of public opinion once we include macro controls (real GDP growth, inflation, unemployment, and whether a country is in a EU/IMF program). Some of the circumstances under which consolidation is undertaken are significant in explaining the effect on public opinion, but also these effects are neither strong nor consistent throughout. We conclude that the effect of fiscal consolidation measures on public opinion mainly operates through their effect on the macroeconomy.
Keywords: H2; H3; H5; H6; 330; Euroscepticism; fiscal consolidation; primary balance; public opinion; trust